Intubating Conditions with Rocuronium Bromide and Suxamethonium in Elective Surgeries: A Randomized Comparative Study - Paudyal, Kanchan Prakash; Baral, Pawan Puspa; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Adequate intubating condition is required to avoid airway trauma and adverse sympathetic responses. Though, Succinylcholine is considered as ideal drug, it has many contraindications. In search of alternative, rocuronium is found to have similar responses in higher doses. Therefore, our aim was to compare the effect of different dosages of rocuronium with sucinylcholine for tracheal intubation and the haemodynamic variables. MATERIAL AND METHODS: A prospective randomized comparative study was conducted in Universal College of Medical Sciences (UCMS-TH) in 90 (American Society of Anaesthesiologists Physical Status I and II) patients with age between 18 to 60 years scheduled for elective surgeries under general anesthesia. They were divided into 3 groups of 30 each using lottery system. Groups 1 and 2 received intravenous rocuronium 0.6mg/kg and 1mg/kg respectively whereas patients in group 3 received intravenous succinylcholine 1.5mg/kg. Under continuous monitoring, tracheal intubation attempt was done at 60 seconds after the administration of drug and intubating conditions were assessed according to Cooper et al four point scale. RESULTS: Only 26.7% of patients in group 1 exhibited excellent intubating condition whereas in groups 2 and 3, excellent intubating condition was exhibited in 100% when muscle relaxant was administered at 60 seconds with highly significant statistical difference between groups 1 and 3 with p value <0.001 without any adverse effects in any of these patients. CONCLUSION: This study concluded that intubating response with inj. succinylcholine 1.5mg/kg is similar to rocuronium 1.0mg/kg and is superior to inj rocuronium 0.6mg/kg, for intubating condition at 60 seconds following the drug administration while using Cooper et al. Score.